2020
DOI: 10.1200/jco.19.03158
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Patient-Reported Outcomes of Atezolizumab Plus Chemotherapy With or Without Bevacizumab Versus Bevacizumab Plus Chemotherapy in Non–Small-Cell Lung Cancer

Abstract: PURPOSE Atezolizumab, bevacizumab, carboplatin, and paclitaxel (ABCP) demonstrated survival benefit versus bevacizumab, carboplatin, and paclitaxel (BCP) in chemotherapy-naïve nonsquamous non–small-cell lung cancer (NSCLC). We present safety and patient-reported outcomes (PROs) to provide additional information on the relative impact of adding atezolizumab to chemotherapy with and without bevacizumab in nonsquamous NSCLC. METHODS Patients were randomly assigned to receive atezolizumab, carboplatin, and paclita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 31 publications
1
63
0
3
Order By: Relevance
“…Fifty-three articles were deemed to meet our preliminary selection criteria , of which 44 articles were selected for the final comprehensive analysis (18-21, 23-30, 32-42, 44-50, 52, 53, 56, 57, 61-70). The results of 6 clinical trials had been reported in multiple platforms: CheckMate 067 (n = 4) (57-60), PACIFIC (n = 3) (54-56), CheckMate 227 (n = 2) (21,22), OAK (n = 2) (31, 32), KeyNote 054 (n = 2) (51,52) and IMpower 150 (n = 2) (42,43). When such duplications were noted, only one was selected for the meta-analysis.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-three articles were deemed to meet our preliminary selection criteria , of which 44 articles were selected for the final comprehensive analysis (18-21, 23-30, 32-42, 44-50, 52, 53, 56, 57, 61-70). The results of 6 clinical trials had been reported in multiple platforms: CheckMate 067 (n = 4) (57-60), PACIFIC (n = 3) (54-56), CheckMate 227 (n = 2) (21,22), OAK (n = 2) (31, 32), KeyNote 054 (n = 2) (51,52) and IMpower 150 (n = 2) (42,43). When such duplications were noted, only one was selected for the meta-analysis.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The clinical trials were further stratified into seven groups according to the treatment regimen as shown in Table 1. The classes are Group A (PD-1/PD-L1 vs Chemotherapy) , Group B (PD-1/PD-L1 + Chemotherapy vs Chemotherapy) (19,(41)(42)(43)(44)(45)(46)(47)(48)(49), Group C (PD-1/PD-L1 vs Placebo) (50-56), Group D (PD-1 vs PD-1+CTLA-4) (21,22,50,(57)(58)(59)(60)(61), Group E (PD-1+CTLA-4 vs CTLA-4) (57-60, 62), Group F (PD-1 vs CTLA-4) (57)(58)(59)(60)63), and Group G (PD-1/PD-L1 vs PD-1/PD-L1 + Chemotherapy) (19,26). The risks for the various types of adverse events within each group were then evaluated.…”
Section: Characteristics Of Clinical Trialsmentioning
confidence: 99%
“…Therapies that block immune checkpoints show longer-lasting responses than traditional chemotherapy and have been approved by the FDA for the treatment of multiple cancer types, such as melanoma, nonsquamous cell carcinoma, OC, etc. (32)(33)(34). However, therapies that block immune checkpoints have low response rates in approximately 10%-30% cancers, which may be related to tumor mutational burden, PD-L1 expression level, IFN signaling and MHC-I loss.…”
Section: Discussionmentioning
confidence: 99%
“…IMpower150 randomized patients with nonsquamous NSCLC to treatment with chemotherapy plus Bevacizumab, chemotherapy plus atezolizumab or chemotherapy plus Bevacizumab and atezolizumab [55,109,110]. The chemotherapy used was Carboplatin, and Paclitaxel.…”
Section: Impower150mentioning
confidence: 99%
“…No improvement in OS was observed for patients with liver metastasis treated with chemotherapy and atezolizumab compared to patients treated with chemotherapy and Bevacizumab [109]. Recent report about safety and patient-reported outcomes of atezolizumab plus chemotherapy and Bevacizumab shows that this drug combination seems tolerable and with manageable toxicities [110]. For patients with nonsquamous NSCLC, with baseline liver metastases, the combination of chemotherapy, Atezolizumab and Bevacizumab could be an important option to consider in the first line.…”
Section: Impower150mentioning
confidence: 99%